Modern adsorbents for heavy metals captured from wastewater into the circular economy - Segneanu Adina-Elena; Cepan Melinda; Cepan Claudiu; Mihailescu Maria; Marin Catalin; Grozescu Ioan; 28th International Symposium on Analytical and Environmental Problems Szeged 2022. november 14-15. (2022)
Intensive industrialization as a requirement of the development of modern society has harmed the environment with severe repercussions on biodiversity, human health and food security. Special efforts are made to set highly effective methods for environmental remediation in the circular economy.
Keywords: Természettudományok; Kémiai tudományok